Optical communication technologies for datacenters - Chongjin XIE (Dianxin kexue, 2016)
Due to the fast growth of internet services,datacenter related traffic has become the major part of the global network traffic.As a main technology for high-speed data transmission,optical communication technologies have been widely used in today's datacenter networks,from a few meter server-to-server interconnects to transoceanic datacenter-to-datacenter optical networks.Here the optical communication technologies for datacenters were reviewed,including technologies connecting datacenters in wider-area networks and metro-area networks as well as optical interconnect technologies within datacenters,and the advantages and disadvantages of some technologies in the networks were discussed.